Tantangan dan Kontroversi Konstitusi dalam Konteks Tata Negara - Aprilia Nabila; Anik Novita; Eiffeliqa Torriq; Neysa Natalie (Kampus Akademik Publiser, 2024)
Abstract. The constitution is the fundamental rule regarding the governance of a country and is very important because it regulates the relationship between state organs, ensures balanced power, establishes the basic principles of the state, and reflects national identity. The constitution contains rules and principles of political and legal entities, generally referring to the guarantee of rights to its citizens. This research applies a normative juridical research method and uses secondary data sources. Many challenges have faced the Indonesian constitution from the early days of independence until now and possibly in the future. In facing the dynamics and challenges of the constitution in Indonesia, it is important to ensure that the constitution is upheld and respected by all parties. In the context of Indonesia's governance, challenges and controversies related to the constitution have become an inseparable part of the country's political and legal dynamics. However, the implementation of the constitution is often confronted with various challenges and polemics. Keywords: Constitution, Fundamental Governance Rules, Relationship Between State Organs, Balance of Power, Rules and Principles of Political Entities, Rules and Principles of Legal Entities Abstrak. Konstitusi adalah aturan dasar mengenai ketatanegaraan suatu negara, dan sangat penting karena mengatur hubungan antara organ negara, memastikan kekuasaan yang seimbang, menetapkan prinsip-prinsip dasar negara, dan mencerminkan identitas nasional. Konstitusi memuat aturan dan prinsip-prinsip entitas politik dan hukum, umumnya konstitusi merujuk pada penjaminan hak kepada warga masyarakatnya. Penelitian ini menerapkan metode penelitian dengan penelitian yuridis normatif dan menggunakan sumber data sekunder. Banyak tantangan yang dihadapi konstitusi Indonesia mulai semenjak awal kemerdekaan hingga sekarang dan bahkan mungkin di masa yang akan datang. Dalam menghadapi dinamika dan tantangan konstitusi di Indonesia, penting untuk memastikan bahwa konstitusi ditegakkan dan dihormati oleh semua pihak. Dalam konteks tata negara Indonesia, tantangan dan kontroversi terkait konstitusi telah menjadi bagian tak terpisahkan dari dinamika politik dan hukum negara. Namun, pelaksanaan konstitusi tidak jarang dihadapkan pada berbagai tantangan dan polemik. Kata Kunci: Konstitusi, Aturan Dasar Ketatanegaraan, Hubungan Organ Negara, Keseimbangan Kekuasaan, Aturan dan Prinsip Entitas Politik, Aturan dan Prinsip Entitas Hukum